SOSIALISASI ACTIVE LEARNING MATEMATIKA MELALUI PERMAINAN KARTU BAGI GURU-GURU SD N 69 KOTA BENGKULU - Nurul Astuty Yensy (DHARMA RAFLESIA, 2019)
The majority of teacher in SD N 69 Bengkulu city still have difficulty how to organize the effective learning. Very rarely do they plan mathematic learning with a real-life approach that enable the student, because they assume that such learning was useless, confusing and time-consuming. Based on the preliminary survey found that in SD N 69 Bengkulu city, the teacher in there still used a conventional method in learning. The teacher rarely used the prop as learning media, as in the matter of multiplication of integers. Whereas making innovative and creative mathematical tool was so easy to be created, so that in this activity  have done "Socialization of active learning of mathematics. Through card game for teachers in SD N 69 Bengkulu city. The method used in this activity include: workshop, demonstration,  discussion, and Monitoring and Evaluation. Before the activity was done, All of teacher did not have knowledge how to make prop "card game". After the workshop was conducted and after completing the practice of making the prop in school, about 84% were produced better and applicable prop. While the other group had not finished completing the "card game" prop because of technical error, but in general (about 99%) the teacher' response to this activity was excellent and their knowledge of the making of card game prop increased.